Підходи до розуміння масової комунікації - Петрушкевич, Марія; Petrushkevych, Mariya (Східноєвропейський національний університет імені Лесі Українки, 2013)
Проаналізовано один із видів комунікації – масову комунікацію, осмислено підходи до її розуміння, зв’язок із масовою культурою. Акцентовано увагу на неоднозначності цього феномену. У масовій комунікації домінують тенденції знеособлення й уніфікації, які одночасно впливають і на збільшення аудиторії поши-рення, так і на зниження діалогічної якості комунікації. This article analyzes one of the communication types – mass communication, conceptualized approaches to its understanding, relationship with mass culture. Attention is focused on the ambiguity of this phenomenon. In mass communication are dominating trends of depersonalization and unification that simultaneously affect both – the increasing spread of the audience, and reduce the quality of dialogic communication. Approaches that connect mass communication with technical means of communication, depersonalization of messages, unification of information and its social significance, mass culture etc. All verbalized features of mass communication, represented by different scientists, gives a clear view of the complexity and ambiguity of this phenomenon, its dependence on mass culture and the characteristics of audiences perception. At the present stage of its development mass communication begins to promote changes (that are sometimes irreversible) on implementation of spiritual needs of people, including religious. The manifestations of religion are increasingly changing and simplifying following samples of mass communication process.
Approaches to Understanding Mass Cmmunication
Keywords: масова культура; mass culture; масова комунікація; mass communication; мас-медіа; media; інформація; information; функції та риси масової комунікації; functions and features of mass communication